Negotiating the cultural and economic outcomes of sport heritage attractions: the case of the National Baseball Hall of Fame. Issue 2 (3rd July 2019) - Ramshaw, Gregory; Gammon, Sean; Tobar, Felipe
ABSTRACT: Contemporary museums must balance their roles as commercial entities and repositories of various, and often dissonant, heritages and histories. Sports museums in particular often have clear commercial and nostalgic aims, particularly through tourist visitation, though the extent to which they represent more challenging narratives remains unclear. This paper examines how one of the most famous sports museums in the world, the National Baseball Hall of Fame (NBHF) in Cooperstown, New York, balances its dual role as tourist attraction and repository of baseball's sometimes checkered past. It was found that different sections of the museum provide greater or lesser degrees of engagement with more controversial issues, although the commercial outputs and appeal of the museum remains clear throughout. Utlimately, the NBHF demonstrates that balancing veneration and critique in collections can be commercially prosperous, and can provide a template for other sport and popular culture museums who may be wary of incorporating more challenging narratives in their exhibits. Furthermore, the symbiotic relationship between the Hall of Fame and the village of Cooperstown, particularly in creating and maintaining cultural and economic outputs, requires further exploration.